2021
DOI: 10.3390/ijerph18115968
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Cardiovascular Health and Lifestyle Status of ‘Health Conscious’ Adult Vegans and Non-Vegans from Slovenia: A Cross-Sectional Self-Reported Survey

Abstract: The study aim was to investigate differences in nutritional, cardiovascular and lifestyle status of ‘health conscious’ subjects. In a partial ‘lock-down’ during the COVID-19 pandemic period, we performed a web-based, cross-sectional study. We compared 80 self-selected subjects (51 vegans, 67% females, and 29 non-vegans, 55% females, p = 0.344). Nutritional status was assessed by bio-electrical impedance and standardized food frequency questionnaires (i.e., contribution of nutrients from foods and supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 63 publications
6
40
0
1
Order By: Relevance
“…Vegan diets have been explored with various study designs (i.e., randomized/nonrandomized (un)controlled, crossover, cross-sectional, a meta-analysis of intervention/observational studies and narrative review) and have shown reduced body mass [56][57][58][59][60][61][62][63][64][65][66][67] and improved body composition status [59,60,[67][68][69][70][71][72][73]. For example, a 12-week randomized controlled trial ("the Broad study") showed substantial body mass loss results in overweight or obese patients with type 2 diabetes or some form of cardiovascular disease within 3 months (−8.6 kg), 6 months (−12.1 kg), and 12 months (−11.5 kg) of follow-up without mandating regular PA or restricting total energy intake [56].…”
Section: Body Mass and Body Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vegan diets have been explored with various study designs (i.e., randomized/nonrandomized (un)controlled, crossover, cross-sectional, a meta-analysis of intervention/observational studies and narrative review) and have shown reduced body mass [56][57][58][59][60][61][62][63][64][65][66][67] and improved body composition status [59,60,[67][68][69][70][71][72][73]. For example, a 12-week randomized controlled trial ("the Broad study") showed substantial body mass loss results in overweight or obese patients with type 2 diabetes or some form of cardiovascular disease within 3 months (−8.6 kg), 6 months (−12.1 kg), and 12 months (−11.5 kg) of follow-up without mandating regular PA or restricting total energy intake [56].…”
Section: Body Mass and Body Compositionmentioning
confidence: 99%
“…Many study designs have shown that a vegan diet successfully reduces common CVD risk factors or is associated with beneficial short-and long-term health effects (i.e., lowdensity lipoprotein cholesterol, triglycerides, blood pressure) [56,60,61,65,67,68,71,[96][97][98][99][100][101][102][103][104][105][106][107]. A meta-analysis of 31 observational studies comparing the effect of a vegan diet with an omnivorous diet on CVD risk factors showed that vegans' average LDL cholesterol values were 2.36 mmol/L, their triglycerides were 1.1 mmol/L and their blood pressure was 118/77 mmHg [63].…”
Section: Cardiovascular Healthmentioning
confidence: 99%
See 3 more Smart Citations